The Organizational Context of Management Accounting (Book). - Leininger, Wayne E.; Meyer, Philip E. (The Accounting Review, 1983)
Abstract Reviews the book "The Organizational Context of Management Accounting," edited by Robert H. Chenhall, Graeme L. Harrison and David J.H. Watson.